A comparative evaluation of catalytic activities of carbon molecular sieve counter electrode toward different redox couples in dye-sensitized solar cells. (10th May 2016) - Li, Xiaowei; Chen, Ruixue; Li, Ling; Wang, Shufang; Zhang, Wenming; Wu, Kezhong; Li, Wenyan; Wu, Mingxing
Abstract: Carbon molecular sieve (CMS) has been proposed as counter electrode (CE) catalyst in dye-sensitized solar cells (DSCs) for the first time. We evaluate the catalytic activities of CMS for the regeneration of different redox couples of I3 − /I −, T2 /T −, and Co 3+/2+, and compare them with those of the traditional Pt CE, which is very expensive. For the I3 − /I − redox couple, the CMS shows a relatively lower catalytic behavior than Pt due to large charge transfer resistance and low mass transport rate. Toward the organic T2 /T − redox couple, the CMS is a much better catalyst than Pt, and the DSCs exhibits a power conversion efficiency (PCE) of 5.30%, which is a great enhancement of 42.09% over the Pt CE based DSCs. Cyclic voltammograms depict that CMS displays a high peak current density and a low peak-to-peak separation, indicating a high catalytic activity of CMS toward T2 /T − redox couple. For the Co 3+/2+ redox couple, CMS presents a competitive catalytic activity relative to Pt and the DSCs shows a PCE of 8.73%.